Agroecological Strategies for Arthropod Pest Management in Brazil - Lemos, Felipe; A. Sarmento, Renato; V. Teodoro, Adenir; R. dos Santos, Gil; R. do Nascimento, Ildon (Recent Patents on Food, Nutrition & Agriculture, 2011)
There is a need to implement a new approach to pest control in which agroecological strategies are developed and adapted in a site-specific way to highly variable and diverse farm conditions typical of farms in tropical regions such as Brazil. It has become evident that the conventional agriculture based on high use of external inputs and oriented to maximize profits, has often been detrimental and unviable when considered from social and ecological perspectives. Pest problems, for example, are generally related to high input, single-crop agroecosystems. We discuss here agroecological strategies such as conservation biological control, use of natural pesticides and selectivity of synthetic and natural pesticides as a way to conserve and increase natural enemies' efficiency in Brazilian agroecosystems. In addition, we discuss some patents related to agroecological pest management.
Keywords: Conservation biological control